Comparison of the effect of two drugs paracetamol with intravenous ibuprofen in patent ductus arteriosus treatment - Mirzarahimi, Mehrdad; Emamzadeghan, Ramin; Enteshari Moghaddam, Afsaneh; Falsafi, Narges (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Patent ductus arteriosus (PDA) is a common cause of morbidity and mortality among premature infants that affects more than 40% of them. PDA treatment includes medical and surgical treatment. Most drugs used to block PDA are cyclooxygenase inhibitors (ibuprofen and indomethacin). The role of paracetamol as an alternative therapy in PDA ligation has been considered in recent years due to the potential side effects of cyclooxygenase inhibitors. Methods: Patients in the first group were treated with intravenous paracetamol at a dose of 15 mg/kg every 6 hours for three days and the second group was treated with intravenous ibuprofen at a daily dose of 10 mg/kg daily and 5 mg/kg for the second and third days. At the end of the treatment period (day 3), they underwent echocardiography again. If the echocardiographic findings indicated no closure of the arterial duct, patients were treated with the aforementioned drug for another period and rechecked at the end of the third day, and at each stage required information was collected. Results: Arterial duct closure in paracetamol group was 96.7% and in ibuprofen group was 100%. The effects of both paracetamol and ibuprofen were similar in terms of renal parameters but in terms of effects on liver parameters. The effect of paracetamol on all liver parameters except aspartate transaminase (AST) was significant, but ibuprofen was able to affect only bilirubin among liver parameters and had no significant effect on both AST and alanine aminotransferase, parameters. Conclusions: Results showed that both paracetamol and ibuprofen are effective in treating of PDA and had similar impact.